Revolusi Digital Dan Kebudayaan Islam - Ega Saputra saputra; Nadila Nadila; Intana Intana; Misiyah Misiyah; Dwi Noviani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The issues addressed in this paper are how the digital revolution influences the development of Islamic culture and the challenges Muslims face in navigating these changes. Furthermore, it is important to understand the positive and negative impacts of the digital revolution on Islamic cultural values. The purpose of this research is to analyze the dynamics of change in Islamic culture within the context of the digital revolution and to identify strategies that can be implemented to maintain and strengthen Islamic values. The research also aims to understand the adaptation of Muslim communities to digital technology. The method used in this research is a qualitative study using a literature analysis approach and observation of the phenomenon of digital technology use within Muslim communities. Data was collected from primary and secondary sources related to digital developments and the dynamics of Islamic culture. The results show that the digital revolution has brought about a major transformation in the way Muslims access, disseminate, and practice their cultural values. In addition to strengthening Islamic communication and education, digital technology also poses challenges in the form of the dissemination of inaccurate information and rapid changes in traditions. Muslim communities must be able to balance cultural preservation with the wise use of technology. In conclusion, the digital revolution has had a significant impact on Islamic culture, requiring an adaptive approach to ensure Islamic values ​​remain relevant and maintained in the digital era. The purpose of this research is to analyze the dynamics of change in Islamic culture within the context of the digital revolution and to identify strategies that can be implemented to maintain and strengthen Islamic values. The research also aims to understand the adaptation of Muslim communities to digital technology. The method used in this research is a qualitative study using a literature analysis approach and observation of the phenomenon of digital technology use within Muslim communities. Data was collected from primary and secondary sources related to digital developments and the dynamics of Islamic culture. The results show that the digital revolution has brought about a major transformation in the way Muslims access, disseminate, and practice their cultural values. In addition to strengthening Islamic communication and education, digital technology also poses challenges in the form of the dissemination of inaccurate information and rapid changes in traditions. Muslim communities must be able to balance cultural preservation with the wise use of technology. In conclusion, the digital revolution has had a significant impact on Islamic culture, requiring an adaptive approach to ensure Islamic values ​​remain relevant and maintained in the digital era.